2009
DOI: 10.1371/journal.pbio.1000027
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Variation in the Human Mutation Rate

Abstract: The mutation rate is known to vary between adjacent sites within the human genome as a consequence of context, the most well-studied example being the influence of CpG dinucelotides. We investigated whether there is additional variation by testing whether there is an excess of sites at which both humans and chimpanzees have a single-nucleotide polymorphism (SNP). We found a highly significant excess of such sites, and we demonstrated that this excess is not due to neighbouring nucleotide effects, ancestral pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
135
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(147 citation statements)
references
References 35 publications
11
135
1
Order By: Relevance
“…However, a recent study using air chromatography found ∼0.364% methylation at cytosines in S. cerevisiae (42). If methylated cytosines in yeast have similar 10×-50× elevations in mutation rate as in humans (43)(44)(45), 1/5-1/25 of all CCG and TCG sites would have to be methylated for the observed ∼2× overall increase in mutation rate at these sites. Taking 0.364% to be the methylation rate in S. cerevisiae and assuming all methylation takes place within CCG and TCG contexts where we found elevated mutation rates, which correspond to ∼3% of the analyzed sequences, this value leads to an estimate of ∼1/22 of CCG and TCG sites being methylated.…”
Section: Discussionmentioning
confidence: 95%
“…However, a recent study using air chromatography found ∼0.364% methylation at cytosines in S. cerevisiae (42). If methylated cytosines in yeast have similar 10×-50× elevations in mutation rate as in humans (43)(44)(45), 1/5-1/25 of all CCG and TCG sites would have to be methylated for the observed ∼2× overall increase in mutation rate at these sites. Taking 0.364% to be the methylation rate in S. cerevisiae and assuming all methylation takes place within CCG and TCG contexts where we found elevated mutation rates, which correspond to ∼3% of the analyzed sequences, this value leads to an estimate of ∼1/22 of CCG and TCG sites being methylated.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, CpGs that have been lost are not causing the excess of triallelic sites. However, we have previously shown that the mutation rate varies across the human genome in a cryptic nature that is not associated with any specific context effect (Hodgkinson et al 2009). This was demonstrated by showing that there is an excess of sites with a SNP at the orthologous position in humans and chimpanzees (coincident SNPs).…”
Section: Excess Of Triallelic Sitesmentioning
confidence: 99%
“…To investigate the effects of cryptic variation in the mutation rate on the number of triallelic sites we used the method described in Hodgkinson et al (2009), but we considered only non-CpG human triallelic SNPs against chimpanzee nonCpG biallelic SNPs. We did not correct for the effects of adjacent nucleotides on the mutation rate since there are not enough data to estimate these for triallelic sites and the effects are small for biallelic sites (Hodgkinson et al 2009).…”
Section: à5mentioning
confidence: 99%
See 2 more Smart Citations